Biographies of Imam Ghazali / Elly Johana Johan, Wan Anisha Wan Mohammad and Azlina Mohd Mydin - Johan, Elly Johana; Wan Mohammad, Wan Anisha; Mohd Mydin, Azlina (Unit Penerbitan Dan Publisiti JSKM, 2022)
• Full name: Abu Hamid Muhammad 1 bin Muhammad bin Muhammad bin Ahmad Al—Ghazali Al-tusi. • Born in year 450H/ 1085M at Ghazalah, Thusia town in Khurasan, Parsi and died on 505h, at age 55.